2020
DOI: 10.1111/1442-1984.12295
|View full text |Cite
|
Sign up to set email alerts
|

Physiological dormancy in seeds of tropical montane woody species in Hawai`i

Abstract: Worldwide, there is relatively little information on seed dormancy and germination of tropical montane species. Our aim was to help fill this knowledge gap by conducting seed dormancy/germination studies on woody species from this vegetation zone in Hawai`i. All species had water‐permeable seeds with a fully developed embryo. Seeds of 29 species (23 genera) were incubated in light/dark at 15/6, 20/10 and 25/15°C and germination monitored at 2‐week intervals for 16–128 weeks. Seeds of Chenopodium oahuense, Duba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…are examples of EF4 species that co‐occurred with B. rockii on Huelo Islet before that species was extirpated there, whose seeds have deep MPD and intermediate or deep PD, respectively (Wolkis et al, 2018 ; Baskin et al, 2021 ). Seeds of D. sandwicensis reached 50% germination at 20/10°C and 20/15°C in 20 weeks (Wolkis et al, 2018 ), and those of O. anthyllidifolia reached 50% germination at 25/15°C and 20/10°C in 17 weeks (Baskin et al, 2021 ). By contrast, we showed that the B. rockii seeds reached 50% germination in 20–26 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…are examples of EF4 species that co‐occurred with B. rockii on Huelo Islet before that species was extirpated there, whose seeds have deep MPD and intermediate or deep PD, respectively (Wolkis et al, 2018 ; Baskin et al, 2021 ). Seeds of D. sandwicensis reached 50% germination at 20/10°C and 20/15°C in 20 weeks (Wolkis et al, 2018 ), and those of O. anthyllidifolia reached 50% germination at 25/15°C and 20/10°C in 17 weeks (Baskin et al, 2021 ). By contrast, we showed that the B. rockii seeds reached 50% germination in 20–26 days.…”
Section: Discussionmentioning
confidence: 99%
“…are examples of EF4 species that co-occurred with B. rockii on Huelo Islet before that species was extirpated there, whose seeds have deep MPD and intermediate or deep PD, respectively (Wolkis et al, 2018;Baskin et al, 2021). Seeds of D. sandwicensis reached 50% germination at 20/10°C and 20/15°C in 20 weeks (Wolkis et al, 2018), and those of O. anthyllidifolia reached 50% germination at 25/15°C and 20/10°C in 17 weeks (Baskin et al, 2021). By contrast, we showed that the B. rockii seeds For many exceptional species, cryobiotechnologies (and, to some extent, in vitro propagation) have been the main focus of preservation research (Pritchard, 2018;Pence et al, 2020;Philpott et al, 2022), but the storage of dry seeds at −18°C would be less expensive than cryobiotechnology.…”
Section: Germination Conditionsmentioning
confidence: 99%
“…The ability of seed-bearing TMCF plants to shift their distribution in response to climate change will depend on the ability of their seed to germinate under new environmental conditions in their current location and/or at higher altitudes. However, our understanding of the regeneration and distribution of tropical montane plant species (Baskin and Baskin 2014;Baskin et al 2021), and particularly TMCF species (Martin and Bellingham 2016), is limited.…”
Section: Introductionmentioning
confidence: 99%